Effects of 4-week astaxanthin supplementation on athletic performance and body composition in young male taekwondo athletes: a randomized, double-blind, placebo-controlled trial - Zhang, Xiu-Chang; Shu, Meng-Yuan; Li, Ke-Min; Wang, Ning; Wang, Xiao-Yu; Shao, Li; Yang, Yong; Liu, Wei; Zhu, Shuai; Zuo, Li; Li, Guo-Qi; Chen, Xiao-Hua; et al. (Frontiers in Nutrition, 2025)
Astaxanthin is an orange-colored natural antioxidant abundantly found in crustaceans and microalgae. It exhibits diverse physiological and protective properties, including anti-inflammatory and antioxidative effects, which make it a promising ergogenic supplement for athletes. This study aimed to investigate the effects of 4 weeks of daily astaxanthin supplementation (12 mg/day) on physical performance and body composition in young male Taekwondo athletes. A randomized, double-blind, placebo-controlled design was employed to ensure the reliability of outcomes. The results showed that astaxanthin supplementation did not produce significant changes in body composition variables such as muscle mass or body fat mass. However, compared with the placebo group, athletes who received astaxanthin exhibited greater improvements in sport-specific kicking performance. Double jump kick performance increased from 67.2 ± 1.8 to 70.1 ± 2.5 kicks/20 s in the astaxanthin group, whereas it remained essentially unchanged in the placebo group (67.9 ± 2.5 to 66.9 ± 2.7 kicks/20 s). Between-group differences in double jump kick performance became statistically significant from week 1 onward and were maintained through week 4 (p < 0.05). Similarly, high roundhouse kick performance improved from 93.2 ± 5.0 to 96.7 ± 4.9 kicks/60 s in the astaxanthin group, compared with 94.7 ± 3.2 to 93.6 ± 3.1 kicks/60 s in the placebo group, with significant between-group differences first detected at week 2 and persisting until week 4 (p < 0.05). These findings suggest enhanced anaerobic capacity and neuromuscular coordination. No adverse effects or gastrointestinal discomfort were reported during the supplementation period, indicating that astaxanthin was well-tolerated. In conclusion, short-term daily supplementation with 12 mg of astaxanthin can safely and effectively improve specific performance parameters in Taekwondo athletes. We recommend continuous intake for at least 2 weeks before competition to optimize performance outcomes.